2022
DOI: 10.29390/cjrt-2022-035
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to achieve adherence to prone positioning in awake COVID-19 patients with highflow nasal oxygen. A case series

Abstract: Introduction:The use of high-flow nasal oxygen (HFNO) is a simple method that can reduce intubation in patients with hypoxemic acute respiratory failure (ARF). Early and prolonged prone position has demonstrated benefits on mortality in mechanically ventilated patients and on intubation in awake patients with ARF. However, strategies to achieve adherence to awake prone positioning (APP) have not been previously described.Case and outcomes: We present six patients with ARF due to COVID-19 treated with HFNO and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Nursing-directed protocols might increase adherence, leading to possible different results 18 . Several strategies including light sedation have been proposed in order to achieve adherence for long prone position sessions 50,51 . An important issue is whether the effect of better oxygenation in prone position in patients with COVID-19 is indeed associated with a reduced intubation rate, even in an ICU setting, where the compliance and monitoring are better than in the ward.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing-directed protocols might increase adherence, leading to possible different results 18 . Several strategies including light sedation have been proposed in order to achieve adherence for long prone position sessions 50,51 . An important issue is whether the effect of better oxygenation in prone position in patients with COVID-19 is indeed associated with a reduced intubation rate, even in an ICU setting, where the compliance and monitoring are better than in the ward.…”
Section: Discussionmentioning
confidence: 99%
“…The study reported many protocol violations, with no patients managing the 12–16 h of proning recommended by providers. A small case series of patients with initial mean P aO 2 / F IO 2 of 121 treated with HFNC showed that implementing a personalised protocol with the active involvement of trained healthcare personnel helped achieve 13 h·day −1 on APP for 20 consecutive days [ 53 ]. Increasing evidence suggests that a simple suggestion of “self-proning” is not enough to achieve prolonged time on APP [ 45 , 47 ] as a therapeutic intervention.…”
Section: App Adherence and Tolerancementioning
confidence: 99%